Strengthening Homestay Management Based On Local Wisdom In The Village Lumban Suhi Suhi Toruan - Siti Hajar; Puji Santoso; Faustyna Faustyna (Universitas Serang Raya, 2022)
The development of the tourism village program at Lumban Suhi Suhi Toruan Village is a priority because it is a creative village producing Ulos Batak. Efforts have been made in developing this tourism village program, one of which is managing homestays. The problems faced by partners are the low awareness of the community about interpreting the concept of tourism about local wisdom as an effort to develop cultural heritage, the lack of good understanding and ability in the community about homestay governance management related to marketing, finance, national standard services in the tourism sector, and not yet organized. neat administration of homestay management and the absence of regulations and Standard Operating Procedures (SOP) for managing homestays in Lumban Suhi Suhi Toruan Village. The method implemented in strengthening the community's understanding and ability about homestays is counseling and socialization about tourism villages based on local wisdom and tourism products (homestays); as well as training and mentoring on service management, marketing and promotion. The results obtained in this activity are increasing the understanding and awareness of local communities in developing a tourism village based on local wisdom through good and correct homestay management in accordance with tourism service standards, the creation of a homestay symbol that shows local wisdom from Lumban Suhi Suhi Toruan Village, namely Kampung Ulos.